(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the pedagogical conditions using linguistic countrystudying material; including students into independent cognitive activity concerned with applying this material; working out purposeful system of cognitive tasks which favour the development of communicative skills etc. Creation and keeping to such conditions have an effective influence on forming future teacher’s professional skills.